2009
DOI: 10.1001/archinternmed.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Diagnostic Tests for Celiac Disease in Individuals With Symptoms Suggestive of Irritable Bowel Syndrome

Abstract: Prevalence of biopsy-proved celiac disease in cases meeting diagnostic criteria for IBS was more than 4-fold that in controls without IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
165
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(179 citation statements)
references
References 47 publications
4
165
2
8
Order By: Relevance
“…In conclusion, this updated meta-analysis, containing data from a further 22 studies published after the previous version (19), demonstrates a pooled prevalence of biopsy-proven CD of 3.3% among individuals with IBS-type symptoms, with a more than four-fold odds of CD, compared with healthy controls, and this was consistent across all IBS subtypes. Despite Adults (with 90% of participants aged >16 years) with a presumed diagnosis of IBS (either according to a clinician's opinion, questionnaire, after negative investigation(s), or meeting specific diagnostic criteria*).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In conclusion, this updated meta-analysis, containing data from a further 22 studies published after the previous version (19), demonstrates a pooled prevalence of biopsy-proven CD of 3.3% among individuals with IBS-type symptoms, with a more than four-fold odds of CD, compared with healthy controls, and this was consistent across all IBS subtypes. Despite Adults (with 90% of participants aged >16 years) with a presumed diagnosis of IBS (either according to a clinician's opinion, questionnaire, after negative investigation(s), or meeting specific diagnostic criteria*).…”
Section: Discussionmentioning
confidence: 58%
“…In 2009 we published a meta-analysis examining the yield of various diagnostic tests for CD in patients meeting diagnostic criteria for IBS, and showed among those with symptoms suggestive of IBS, the prevalence of biopsy-proven CD was four-fold that of controls without such symptoms (19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that symptoms compatible with IBS may co-exist in patients with several organic GI diseases, such as inflammatory bowel disease, coeliac disease, or bile acid diarrhea, [15][16][17] and that some patients who meet criteria for IBS may have one of these underlying organic diseases. [18][19][20][21] Microscopic colitis (MC) consists of two primary subtypes: collagenous and lymphocytic colitis. Collagenous colitis (CC) differs from lymphocytic colitis (LC) in that it presents a sub-epithelial collagen band adjacent to the basal membrane, whereas the hallmark of LC is a dense lymphocytic infiltration in the epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…7 Individuals with IBS are more likely to consume health care resources than healthy individuals, 8 with up to 80% of sufferers consulting their primary care physician as a result of symptoms. 9,10 Diagnosing IBS can be challenging due to overlap between the symptoms that sufferers report and those of organic GI conditions such as celiac disease, [11][12][13] small intestinal bacterial overgrowth, 14 bile acid diarrhea, 15,16 exocrine pancreatic insufficiency, 17 or inflammatory bowel disease. 18 Partly as a result of this uncertainty, symptom-based diagnostic criteria were developed for use by physicians consulting with patients with suspected IBS as early as the 1970s, with Manning et al reporting six symptoms that were commoner among individuals found ultimately to have IBS after investigation.…”
Section: Introductionmentioning
confidence: 99%